The economics and regulation of network industries : telecommunications and beyond - Vogelsang, Ingo (Cambridge : Cambridge University Press, 2021)
Have you ever wondered how your telephone company or Internet service provider can give you access to almost all people in the world, or how electricity suppliers can compete with each other if there is only one electric supply line passing through your street? This Element deals with the economics and public regulation of such network industries. It puts particular emphasis on the specific economic concepts used for analyzing them and on the regulatory reform movement and the compatibility of regulation and competition. Worldwide most of these industries have changed dramatically in recent years, telecommunications in particular. Network industries mostly exhibit economies of scale in production and similar economies in consumption. Both of these properties cause market power problems that often require industry-specific regulation. However, due to technological and market changes network policies have moved on from end-user regulation to wholesale regulation and in some cases to deregulation.
Title from publisher's bibliographic system (viewed on 07 Oct 2021).
Keywords: Public utilities -- Economic aspects; Public utilities -- Standards; Public utilities -- Government policy; Information networks -- Economic aspects; Information networks -- Standards; Information networks -- Government policy